Repeat measurements of high sensitivity troponins for the prediction of recurrent cardiovascular events in patients with established coronary heart disease: an analysis from the KAROLA study - Jansen, Henning; Schöttker, Ben; Brenner, Hermann (Journal of the American Heart Association, 2019)
Background: High‐sensitivity cardiac troponins T and I (hs‐cTnT and hs‐cTnI) are established biomarkers for myocardial injury and used for diagnostic and prognostic purposes. However, whether repeat measurements improve prediction of recurrent cardiovascular disease (CVD) events in patients with stable coronary heart disease (CHD) after adjustment for several other novel biomarkers remains unclear.Methods and ResultsWe measured both troponins in 873 coronary heart disease patients from the KAROLA (Langzeiterfolge der Kardiologischen Anschlussheilbehandlung) study about 9 weeks after their initial acute event (baseline) and after 12 months, followed them for 12 years, assessed a combined CVD end point, and adjusted for several risk factors. As we found evidence for effect modification, results were stratified according to presence of myocardial infarction at baseline. During follow‐up, 186 fatal and non‐fatal CVD events occurred. Both baseline and 12‐months troponin concentrations were significantly associated with CVD events in patients without myocardial infarction at baseline; in tendency 12 months of troponin showed stronger hazard ratios (hs‐cTnT: hazard ratios 1.91 (95% CI 1.17-3.11) versus baseline values 1.71 (95% CI 1.08-2.70) and for hs‐cTnI: hazard ratio 1.55 (95% CI 1.05-2.30) versus baseline value 1.22 (95% CI 0.88-1.68) in the fully and simultaneously adjusted model.ConclusionsBoth troponins are consistently associated with recurrent cardiovascular events after adjustment for emerging risk factors during follow‐up in our study especially evident in patients without myocardial infarction at baseline. Troponin values at 12 months of follow‐up showed independent associations with future CVD events in addition to baseline assessments of troponins.
Gesehen am 22.07.2019